Gerechter Frieden: Das fortwährende Dilemma militärischer Gewalt - Werkner, Ines-Jacqueline (transcript, 2018)
Just peace stands for a fundamental change of applied ethics: The focus of this new concept is no longer on war but rather on peace in its mutual relatedness to justice. Yet the question of using armed force remains to be of central importance even for just peace. Ines-Jacqueline Werkner shows: The current discourse on the international responsibility to provide protection and the conflict between the protection of humans in danger and the nonviolence envisaged that goes with it reveal contradictions and controversies. Even the ecumenical debate about just peace is significantly shaped by ecclesiastical divergences.